Chemical analysis of arabica coffee (Coffea arabica l.) and defective beans submitted to different degrees of roasting - Morais, Sérgio Antônio Lemos de; Aquino, Francisco José Tôrres de; Chang, Roberto; Nascimento, Evandro Afonso do; Oliveira, Grasielle Silva de; Santos, Neide Carolina dos (Coffee Science - ISSN 1984-3909, 1970)
The present work studied the chemical composition of arabica coffee (Coffea arabica L.) and defective beans (black, green and brown beans), from the same origin, submitted to different degrees of roasting. The coffee samples came from the Minas Gerais savannah (“cerrado”). The beverages prepared from defective beans were sourer, probably due to beans fermentation. Also, the presence of defective beans reduced the essential oil concentration and raised the levels of undesirable compounds in the aroma, such as low molecular mass, aldehydes, and sulfides. Otherwise, the defective and good coffee bean substrates were quite similar, composed mainly of carbohydrates, proteins, lipids, ash, phenols, carboxylic acids, trigonelline, and caffeine. Extended roasting reduced the difference between the odor activity of the potent odorants in the two analyzed beverages, making it more difficult to distinguish their aromas.